2020
DOI: 10.1101/2020.02.25.20027763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and clinical features of 2019 novel coronavirus disease (COVID-19) in the Fever Clinic of a teaching hospital in Beijing: a single-center, retrospective study

Abstract: Background With the spread of COVID-19 from Wuhan, Hubei Province to other areas of the country, medical staff in Fever Clinics faced the challenge of identifying suspected cases among febrile patients with acute respiratory infections. We aimed to describe the prevalence and clinical features of COVID-19 as compared to pneumonias of other etiologies in a Fever Clinic in Beijing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
5
16
0
2
Order By: Relevance
“…In the first analysis however, despite a trend of lowered lymphocyte count in COVID-19 cases, no statistical significance was observed between the two groups. The possible reason for the insignificant difference between the pooled studies of both groups is that two studies 19,21 included in the analysis showed higher tendency of lymphopenia to occur in the non-COVID group. However, in the second analysis lymphocyte counts were found significantly lower in the severe group, which is in line with previous reports which observed progressive lymphopenia 41 as a strong indicator of disease severity.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the first analysis however, despite a trend of lowered lymphocyte count in COVID-19 cases, no statistical significance was observed between the two groups. The possible reason for the insignificant difference between the pooled studies of both groups is that two studies 19,21 included in the analysis showed higher tendency of lymphopenia to occur in the non-COVID group. However, in the second analysis lymphocyte counts were found significantly lower in the severe group, which is in line with previous reports which observed progressive lymphopenia 41 as a strong indicator of disease severity.…”
Section: Discussionmentioning
confidence: 93%
“…Relative to non-COVID-19 infections, significantly lower absolute leukocyte or neutrophil counts during early stages of the disease has been broadly demonstrated, 15,18,21 although the mean leukocyte count of the included studies often do not exceed the lower limit for categorisation as leukopenia or neutropenia. Interestingly, with COVID-19 disease progression, we found that both leukocyte and neutrophil counts were significantly higher in the severe groups in line with previous retrospective studies, 41 and other meta-analysis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These symptoms are identifiable without specific examinations that are directly documented in the patient's medical record. Liang et al [8] mention that for most patients diagnosed with COVID-19, 85.7% had fever, 42.9% had cough, 33.3% had expectoration, 57.1% had fatigue and 38.1% had headache and dizziness. For this reason, one can see that fever is a common symptom.…”
Section: Introductionmentioning
confidence: 99%
“…On January 19, 2020, two cases in Beijing and one case in Guangdong Province were reported, and subsequently more cases were reported elsewhere. 3 This is a viral respiratory infection, SARS-CoV-2 or COVID-19 can be transmitted through the respiratory tract. It mainly causes respiratory tract infections and develops severe pneumonia in infected patients.…”
Section: Introductionmentioning
confidence: 99%